A retrospective evaluation of Alvarado score in diagnosing acute appendicitis in a tertiary care hospital at Pondicherry - Ray, G.; Selvakumaran, S. (International Surgery Journal, 2021)
Background: Acute appendicitis is a common and sometimes confusing cause of acute abdomen in all age groups. Diagnosis of appendicitis can be difficult, occasionally taxing the diagnostic skills of even the most experienced surgeon. Despite the increased use of USG, CT, the rate of misdiagnosis of appendicitis has remained the same (15.3%). To evaluate the usefulness of the Alvarado score as a simple and reliable tool in preoperative diagnosis of acute appendicitis. Methods: This retrospective study conducted on 97 cases includes all patients who were admitted with a clinical diagnosis of acute appendicitis for a period of one year from February 2019 to January 2020 at IGMCRI Pondicherry with clinical suspicions of acute appendicitis were included in the study. The modified scoring system is based on 3 signs, 3 symptoms, and 1 laboratory finding. The patient was classified as males, females, and children (<12 years). These were further grouped based on the scores 7-9, 5-6, and <5. Results: A total of 80 patients with a score of 7-9 and 5-6 were operated on. Among males with a score of 7-9, 35 patients were operated and 34 were found to have an inflamed appendix. Females with scores 7-9, 16 were operated and 11 were found to have an inflamed appendix. Conclusions: Alvarado scores significantly reduce the number of negative laparotomies without increasing the overall rate of appendicular perforation. It is very effective in men and children but diagnostic laparoscopy or ultrasonography is advised to minimize the high false-negative rate in women.